Desarrollo e implementación de una aplicación móvil con tecnología Android utilizando la metodología Mobile-D, para el acceso inalámbrico a la gestión académica de los estudiantes para la Universidad Técnica de Machala - Balcázar Pesantez, Jhonny Alexander (2014)
The Technical University of Machala has a high growth technology, providing an online service via the computer system referred SIUTMACH, which consists of academic management automation; today in Ecuador has increased the number of users of smartphones "Smartphone", many of these users are people who are studying at university.